Revitalizing Waqf Governance Through Digital Innovation: A Sharia Perspective on Transparency and Public Accountability - Ismaul Fitroh; Firdaus Jeka; Samsul Arifin; Fitrahtul Saahira Khairunnisa`; Erniati Erniati (Indonesian Journal of Sharia and Islamic Sciences, 2026)
The rapid expansion of digital technology has transformed the governance of waqf institutions, creating new opportunities to enhance transparency, accountability, and operational efficiency while simultaneously raising challenges regarding Sharia compliance and institutional legitimacy. This study aims to formulate an integrated framework for revitalizing waqf governance through digital innovation from a Sharia perspective on transparency and public accountability. The research employed a non-empirical qualitative design using a doctrinal and literature-based approach. Data were collected from recent scholarly publications, legal studies, and academic literature concerning waqf governance, digital transformation, Islamic social finance, and maqāṣid al-sharīʿah, followed by critical content analysis and conceptual synthesis. The findings indicate that digital technologies, including blockchain, artificial intelligence, digital accounting, and integrated information systems, strengthen governance effectiveness only when implemented within a governance structure guided by the principles of amanah, justice, transparency, and public welfare. The study further demonstrates that public accountability should be understood as a continuous ethical and institutional process rather than merely financial reporting. The proposed integrated governance model contributes to contemporary Islamic legal scholarship by connecting technological innovation with Sharia governance principles and provides a conceptual foundation for future empirical studies on sustainable digital waqf governance.